2016
DOI: 10.1111/imm.12648
|View full text |Cite
|
Sign up to set email alerts
|

T follicular helper cell programming by cytokine‐mediated events

Abstract: Summary CD4+ T cells, or T helper cells, are critical mediators and coordinators of adaptive immunity. Unique effector T helper cell populations have been identified that perform distinct functions in response to pathogenic infection. The T follicular helper (Tfh) cells are one such subset, which has been identified as the primary T-cell population responsible for interacting with B cells to promote effective antibody-mediated immune responses. Since their initial description at the turn of the century, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 98 publications
(270 reference statements)
2
25
0
Order By: Relevance
“…As discussed previously, signals from environmental cytokines are key determinants of T helper cell differentiation. These include IL-6 and IL-2, which have been shown to positively and negatively influence T FH development, respectively (21, 57, 58). Therefore, we wanted to assess whether Aiolos or Ikaros may play a broader role in promoting T FH cell differentiation by regulating the expression of the receptors for these cytokines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed previously, signals from environmental cytokines are key determinants of T helper cell differentiation. These include IL-6 and IL-2, which have been shown to positively and negatively influence T FH development, respectively (21, 57, 58). Therefore, we wanted to assess whether Aiolos or Ikaros may play a broader role in promoting T FH cell differentiation by regulating the expression of the receptors for these cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…STAT3, STAT5) at the Bcl6 promoter is an important contributor to the regulation of Bcl-6 expression (21, 57, 58). Unexpectedly, our findings demonstrate that STAT3 physically interacts with Aiolos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follicular T helper cells (Tfh) are the major T cell lineage which promotes B cells maturation and proliferation to produce antibodies for regulating humoral immune response (Qi, ; Walters & Vinuesa, ). During a disease condition, Tfh cells produce large amounts of IL‐21 for B cell differentiation to mediate pathogenic clearance after which it is subdued (Read, Powell, & Oestreich, ). Bryant et al () reported that huge quantities of immunoglobulin (Ig) subtypes (IgG, IgM, and IgA) were mediated through the presence of IL‐21 as a precursor for Tfh cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…The T‐cell–B‐cell interactions through surface proteins provide further signals allowing pre‐Tfh cells to enter the B‐cell follicles and facilitate the germinal center (GC) reaction. Several cytokines, such as interleukin‐6 (IL‐6), IL‐21 and IL‐12 have been involved in the development of Tfh cells …”
mentioning
confidence: 99%